Pelatihan Pengemasan Produk Pangan Olahan di Desa Sukamahi Kabupaten Bogor - Dewi Ayu Kusumaningrum; Ramon Hurdawaty; Heru Suheryadi; Maryetti; Ni Made Dwiyana Rasuma Putri (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Sukamahi Village is located in Megamendung District, Bogor Regency, West Java, one of the pilot villages for the One Billion One Village (SaMiSaDe) program in 2021. Sukamahi Village has agricultural and plantation potential. Most of the village residents have professions as farmers and own businesses such as food businesses and grocery stores in Sukamahi Village. Most of the women in Sukamahi Village are involved in PKK activities, farming and are housewives. Currently, there are no profitable business activities among the group of women residents of Sukamahi village. There are problems in various regions where local food businesses are generally less attractive, innovative, creative, and the majority are only wrapped in transparent plastic without any labels or information. The aim of organizing this community service is to provide knowledge about packaging processed food products that comply with good food packaging rules and can attract consumers' attention. The implementation method consists of initial observations and training activities. Initial observations include licensing, mapping communities that need training, and formulating appropriate training. The training activity provided material and direct practice in making appropriate products and packaging, ended with a question and answer session regarding what had been provided. Overall, the training on packaging processed food products went well and was beneficial for improving the skills and business marketing of the Sukamahi Village community. With more attractive and quality packaging, processed food business products from Sukamahi Village have a better opportunity to penetrate a wider market to help improve the economic level of business actors.